The Measurement Model of the Pharmacy Education Service Quality: An Empirical Quest Based on Two Approaches - Gupta, Hemant; Parmar, Bhaveshkumar J (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The objective of this study to build a comprehensive model to measure the service quality of the pharmaceutical institutes in India. At the same time, the author also validates the model with two different approaches of service quality measurement that belongs to gap score and perception-only measure. Materials and Methods: The eight pharmacy institutes are selected randomly from eastern India and then 370 respondents take part in this survey process. The model has been developed with exploratory and confirmatory factor analysis based on perception-only and gap (perception minus expectation) scores. Finally, the model has been validated with discriminate validation and OLS regression methods. Finding: The conclusion of this study belongs to a comprehensive model to measure the service quality of pharmacy institutes with the help of 14 variables under 4 latent factors of education service quality. This model may be applied to any pharmacy institute that is offering a graduate pharmacy program. Practical Application: For academician, this study provides a new comprehensive model which is applicable for any approach of measuring the service quality of pharmaceutical education institutes in India. Simultaneously, this model might provide a road map to the Government for improving the quality of education in the pharmacy education system.
Keywords: Pharmacy education; Service Quality; SERVIQUAL; SERVIPERF; Indian Pharmacy Institutes